KORELASI PENGUASAAN KOSAKATA BIDANG LINGKUNGAN HIDUP DENGAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 18 PADANG - Selvimar, Eed; Gani, Erizal (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this research there are three. First, describe the environmental field vocabulary mastery of grade VIII SMP Negeri Padang 18. Second, it describes the writing skills text beritasiswa class VIII SMP Negeri Padang 18. Third, vocabulary mastery correlation describes the environmental field with the text of the news writing skills of students of class VIII SMP Negeri Padang 18. The theory associated with this research is a theory about the writing skills (a), (b) the text of the news, and (c) mastery of the vocabulary of the field of the environment. This research type is quantitative descriptive method. The design used is a korelasional design. Population research is grade VIII SMP Negeri Padang 18 listed on the school year 2018/2019, namely 362 students. The research sample is determined by proportional random sampling of 20% of the population, namely 72 students. Research data in the form of score vocabulary mastery test results of the environmental field and score the writing skills test result text news. The data obtained through two types of tests i.e. objective tests to measure mastery of the vocabulary of the field of environmental and performance tests for measuring writing skills text news. Based on the results of the study, it was concluded that vocabulary knowledge is correlated with writing skills text news. The better knowledge of vocabulary will be the better text news writing skills anyway. Thus, for the skilled writing text news grade VIII SMP Negeri Padang, 18 required mastery of the vocabulary. Kata kunci: Korelasi, Kosakata, Menulis, Teks Berita